2002
DOI: 10.1002/ijc.10409
|View full text |Cite
|
Sign up to set email alerts
|

NS‐398, a selective cyclooxygenase 2 inhibitor, inhibited cell growth and induced cell cycle arrest in human hepatocellular carcinoma cell lines

Abstract: Cyclooxygenase 2 (COX-2) has been suggested to be associated with liver carcinogenesis. Several reports have shown that NSAIDs inhibit the growth of hepatocellular carcinoma cell lines. There is little evidence of how COX-2 inhibitors regulate the proliferation of hepatocellular carcinoma cells or the mechanism involved. In our study, we investigated the growth-inhibitory mechanism of a selective COX-2 inhibitor, NS-398, in 4 hepatocellular carcinoma cell lines by studying cell growth, COX-2 and proliferating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
55
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 21 publications
8
55
1
Order By: Relevance
“…Another large population-based survey reported that the use of NSAIDs significantly reduced the risk of both gastric and oesophageal carcinoma (Farrow et al, 1998). Although the precise mechanisms by which NSAIDs, and COX-2 selective inhibitors in particular, modulate tumour growth have not been elucidated, it appears that cell cycle arrest and apoptosis may play a critical role (Chang and Weng, 2001;Grosch et al, 2001;Cheng et al, 2002;Joe et al, 2002;Kundu et al, 2002;Toyoshima et al, 2002). Alternatively, Sawaoka et al (1998) and Tsujii et al (Tsujii and DuBois, 1995;Sawaoka et al, 1998;Tsujii et al, 1998) have suggested that a decrease in angiogenesis may account for the inhibitory properties of COX-2 selective NSAIDs on tumour growth.…”
Section: Discussionmentioning
confidence: 99%
“…Another large population-based survey reported that the use of NSAIDs significantly reduced the risk of both gastric and oesophageal carcinoma (Farrow et al, 1998). Although the precise mechanisms by which NSAIDs, and COX-2 selective inhibitors in particular, modulate tumour growth have not been elucidated, it appears that cell cycle arrest and apoptosis may play a critical role (Chang and Weng, 2001;Grosch et al, 2001;Cheng et al, 2002;Joe et al, 2002;Kundu et al, 2002;Toyoshima et al, 2002). Alternatively, Sawaoka et al (1998) and Tsujii et al (Tsujii and DuBois, 1995;Sawaoka et al, 1998;Tsujii et al, 1998) have suggested that a decrease in angiogenesis may account for the inhibitory properties of COX-2 selective NSAIDs on tumour growth.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported for pancreatic and colorectal cancer and HCC cell lines. 4,9,30) Some mechanism different from COX-2 expression and PG production might be involved in growth inhibition by etodolac in HCC cells. To understand the mechanism of growth inhibition of HCC by COX-2 inhibition, we studied how etodolac regulates the expression of several key cell cycle regulatory proteins and growth factor signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…5,8) A recent report of ours has also shown that NS-398, a selective COX-2 inhibitor, inhibited growth and induced cell cycle arrest in HCC cell lines. 9) However, the mechanism by which COX-2 inhibitors cause growth inhibition and cell cycle arrest in HCC cells is not known.…”
mentioning
confidence: 99%
“…COX-2 inhibitor is a chemoprevention agent for colon cancer, and its use has been proposed recently (69,70) to decrease the incidence of other types of cancer including gastric and lung cancer. COX-2 inhibitor is used to treat hepatoma (71,72), but its role in prevention is not clearly defined (73). Recently a COX-2 inhibitor was shown to prevent hepatocarcinogenesis in an animal model (74).…”
Section: Fig 3 Activation Of Nf-b During Er Stressmentioning
confidence: 99%